Computer Vision Theory and Projects in Python for Beginners - Sciences, AI (Packt Publishing, 2021)
Explore the world of Computer Vision and learn to master it using Python, OpenCV, TensorFlow, and others About This Video Relate the concepts and theories in Computer Vision with real-world problems Know the theoretical and practical aspects of Computer Vision concepts Build applications for change detection in the live feed of cameras using Computer Vision techniques with Python In Detail The high-quality content of the Mastering Computer Vision from the Absolute Beginning Using Python course presents you with a great opportunity to learn and become an expert. You will learn the core concepts of the CV field. This course will also help you understand the digital imaging process and identify the key application areas of CV. The course is easy to understand, descriptive, comprehensive, practical with live coding, and rich with state-of-the-art and updated knowledge of this field. Although this course is a compilation of all the basic concepts of CV, you are encouraged to step up and experience more than what you learn. Your understanding of every concept is tested at the end of each section. The homework assignments/tasks/activities/quizzes along with solutions will assess your learning. Several of these activities are focused on coding so that you are ready to run with implementations. The two hands-on projects in the last section--Change Detection in CCTV Cameras (Real-Time) and Smart DVRs (Real-Time)--make up the most important learning element of this course. They will help you sharpen your practical skills. Successful completion of these two projects will help you enrich your portfolio and kick-start your career in the CV field. By the end of the course, you will have a strong understanding of Computer Vision concepts and will be ready to apply them in your future projects. Who this book is for This course is useful for data scientists, machine learning experts, and learners who are absolute beginners and know nothing about Computer Vision, and for people who want to learn Computer Vision with real data along with its implementation in realistic projects.